(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
This article proposes a solution to the double slit experiment of Quantum Mechanics. We attack the problem from a previously untried angle. Unsolved math problems must be attacked from unexpected angles because every conventional approach has already been tried and failed. Richard Feynman warned that the quantum world is such a strange place that humans can’t understand it. There is empirical evidence of particles following zero energy waves backwards, although that is counterintuitive. Schr˝odinger waves carry zero energy: they carry probability amplitudes instead. In our proposed model zero energy Schr˝odinger waves emanating from every point on the target screen pass backwards through the two slits, interfere at the particle gun, and a particle randomly chooses which wave to follow backwards. Once that decision is made the particle follows its wave with a probability of one, through only one slit (it doesn’t matter which slit) and inevitably strikes that point from which its wave emanates. This produces the same math and same pattern on the target screen. We propose three Axioms of the Theory of Elementary Waves (TEW) as a better platform for mathematics in this experiment than the Axioms of QM. This constitutes a paradigm shift.